Changes in refraction and contrast sensitivity following short term orthokeratology treatment in high myopic school children: a pilot study - Bariah Mohd-Ali; Tan, Bay Wah; Norhani Mohidin (Universiti Kebangsaan Malaysia, 2014)
It is well established the efficacy of orthokeratology (OK) treatment in improving refraction and visual acuity (VA) of low myopic subjects. However, limited data is available on high myopes. The purpose of this study was to investigate the changes of refraction, VA and contrast sensitivity (CS) over time in high myopic school children after 1 week of overnight OK treatment. A total of 19 high myopic school children were fitted with OK lenses. Mean refraction at baseline was -6.29±1.25 DS. Refraction was conducted using cross cylinder method and LogMAR chart. CS was evaluated using Pelli-Robson and FACT charts. All measurements were taken at baseline, 1, 2, 3 and 7 days after overnight OK. Data was analyzed using repeated measures of ANOVA. The results showed that refraction and CS were significantly improved throughout the study period (p<0.05). Significant changes in all parameters were noted after the first overnight treatment. Mean refraction and unaided VA after 7 nights of treatment was -0.64±1.17DS and 0.08±0.29, respectively. The results from Pelli-Robson and FACT charts showed improvement comparable to aided baseline values (p>0.05). This study concludes that overnight OK reduces refraction but does not compromise VA and CS in high myopic children within the study period. Further studies are needed to determine the long term impact of OK treatment on visual functions in a larger sample of high myopic children.